Analysis of geomagnetic hourly ranges. Issue 8 (7th August 2015) - Danskin, D. W.; Lotz, S. I.
Abstract In an attempt to develop better forecasts of geomagnetic activity, hourly ranges of geomagnetic data are analyzed with a focus on how the data are distributed. A lognormal distribution is found to be able to characterize the magnetic data for all observatories up to moderate disturbances with each distribution controlled by the mean of the logarithm of the hourly range. In the subauroral zone, the distribution deviates from the lognormal, which is interpreted as motion of the auroral electrojet toward the equator. For most observatories, a substantial deviation from the lognormal distribution was noted at the higher values and is best modeled with a power law extrapolation, which gives estimates of the extreme values that may occur at observatories which contribute to the disturbance storm time (Dst) index and in Canada.